Building Perinatal Pathology Research Capacity in Sub-Saharan Africa - Bebell, Lisa M.; Ngonzi, Joseph; Meier, Frederick A.; Carreon, Chrystalle Katte; Birungi, Abraham; Kerry, Vanessa B.; Atwine, Raymond; Roberts, Drucilla J. (Frontiers in Medicine, 2022)
Introduction Over two million stillbirths and neonatal deaths occur in sub-Saharan Africa (sSA) annually. Despite multilateral efforts, reducing perinatal mortality has been slow. Although targeted pathologic investigation can often determine cause of perinatal death, in resource-limited settings stillbirths, early neonatal deaths, and placentas are rarely examined pathologically. However, the placenta is a key source of diagnostic information and as the main determinant of fetal growth and development in utero, influencing child health outcomes. Method In 2016, our collaborative intercontinental group began investigating infectious perinatal death and adverse child health outcomes in Uganda. We developed and initiated a 4-day combined didactic/practical curriculum to train health workers in placental collection, gross placental examination, and tissue sampling for histology. We also trained a local technician to perform immunohistochemistry staining. Results Overall, we trained 12 health workers who performed gross placental assessment for >1,000 placentas, obtaining >5,000 formalin-fixed tissue samples for research diagnostic use. Median placental weights ranged from 425 to 456 grams, and 33.3% of placentas were <10th percentile in weight, corrected for gestational age. Acute chorioamnionitis (32.3%) and maternal vascular malperfusion (25.4%) were common diagnoses. Discussion Through a targeted training program, we build capacity at a university-affiliated hospital in sSA to independently perform placental collection, gross pathologic examination and placental tissue processing for histology and special stains. Our training model can be applied to other collaborative research endeavors in diverse resource-limited settings to improve research and clinical capacity and competency for diagnostics and management of stillbirth, neonatal death, and child health outcomes.